2013
DOI: 10.1111/ijfs.12083
|View full text |Cite
|
Sign up to set email alerts
|

Production and stability of water‐dispersible astaxanthin oleoresin from Phaffia rhodozyma

Abstract: The process of extracting the astaxanthin oleoresin from pretreated Phaffia rhodozyma cells was optimised using a Box-Behnken response surface design. Microwaving the cells at 105 W for 1 min followed by ethyl acetate extraction was the best pretreatment, and the optimal extraction conditions were 65°C for 24 min using a solvent-solid ratio of 19:1. The order of the ability to disperse the astaxanthin oleoresin was propylene glycol> Tween 80 > Tween 20 > a-cyclodextrin, b-cyclodextrin. It was determined that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Conversely, the bioavailability of astaxanthin was higher when used with protein-based ingredients, especially milk. The greatest stability of astaxanthin oleoresin from P. rhodozyma dispersed in aqueous solution of propylene glycol was noted at pH 4 and at low temperatures (Villalobos-Castillejos et al 2013). Moreover, Peng et al (2010) observed improved stability and bioavailability of astaxanthin when encapsulated within liposomes.…”
Section: Storage Stability Of Astaxanthinmentioning
confidence: 94%
See 1 more Smart Citation
“…Conversely, the bioavailability of astaxanthin was higher when used with protein-based ingredients, especially milk. The greatest stability of astaxanthin oleoresin from P. rhodozyma dispersed in aqueous solution of propylene glycol was noted at pH 4 and at low temperatures (Villalobos-Castillejos et al 2013). Moreover, Peng et al (2010) observed improved stability and bioavailability of astaxanthin when encapsulated within liposomes.…”
Section: Storage Stability Of Astaxanthinmentioning
confidence: 94%
“…The greatest stability of astaxanthin oleoresin from P. rhodozyma dispersed in aqueous solution of propylene glycol was noted at pH 4 and at low temperatures (Villalobos‐Castillejos et al . ). Moreover, Peng et al .…”
Section: Storage Stability Of Astaxanthinmentioning
confidence: 97%
“…Extraction by organic solvents, centrifugation, macroporous resin separation and solid‐phase extraction with cartridges are frequently used for sample pretreatment (Lichtenberg et al ., ; Villalobos‐Castillejos et al ., ). For example, a gas chromatography with nitrogen–phosphorus detector analytical method was reported to determine caffeine isolated from the coffee by liquid–liquid extraction before analysing (Mccusker et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Chemical synthesis of astaxanthin would inevitably lead to the introduction of toxic chemical impurities. Therefore, it is preferentially obtained from natural sources such as the Haematococcus pluvialis ( H. pluvialis ) (Kim et al ., ), the yeast Phaffia rhodozyma (Villalobos‐Castillejos et al ., ), or shrimp, crab and other crustaceans (Mao et al ., ). Astaxanthin has a variety of geometric isomers, such as 9‐ cis , 13‐ cis and all‐ trans , of which all‐ trans configuration is the most stable structure (Fig.…”
Section: Introductionmentioning
confidence: 99%